Основні напрямки підвищення ефективності використання основних засобів підприємства в сучасних умовах - Смоловик, Раїса Федорівна (НТУ "ХПІ", 2016)
У статті проаналізовані проблеми ефективного використання основних засобів та необхідність моніторингу показників їх використання у конкретних умовах підприємства з метою підвищення продуктивності. Розглянуті питання створення і освоєння нових видів продукції та підвищення її якості після проведення модернізації обладнання. Проведений розрахунок деяких організаційно-технічних заходів спрямованих на підвищення ефективності використання основних засобів.

The article analyzes the problems of efficient use of fixed assets and the need for monitoring indicators of their use in specific conditions of the enterprise with the aim of increasing productivity. Considers creation and development of new products and improvement of its quality after modernization of equipment. Analyzed stages, the sequence of events contributing to the improvement in the use of equipment for the time factor and performance. The calculations of certain organizational and technical measures directed on increase of efficiency of use of fixed assets due to the factors: improving the shift coefficient of the equipment, increasing the productivity of basic production workers performing work in conditions of modernized equipment. Analyzed the possible terms of reducing the cost of production and its cost.
Basic directions of increase of efficiency of use of fixed assets of the enterprise in modern conditions
Keywords: модернізація; моніторинг; продуктивність; планування; управління; modernization; monitoring; planning